An anisotropic mesoscale model of fatigue failure in a titanium alloy containing duplex microstructure and hard α inclusions. (August 2020) - Hu, Dianyin; Pan, Jinchao; Mao, Jianxing; Guo, Xiaojun; Ji, Haibin; Wang, Rongqiao
Abstract: Fatigue life estimation on hard α inclusion induced failure in titanium alloy remains in long-term interest, due to the local stress distribution induced by the interaction between inclusion and surface as well as the scatter in randomly oriented grains. In this paper, an anisotropic mesoscale model is established to describe the fatigue failure of typical bi-phase titanium alloy with hard α inclusion. The stress-life criterion is formulated by dislocation stress field elaborated from anisotropic fracture mechanics, taking in random variables to represent the scatter in grain size and orientation. Parameters include microstructures characterized by microscope, dislocation slip properties evaluated by molecular dynamics (MD) simulation, and information of activated slip system via crystal plasticity finite element method (CPFEM) simulation. By using the data of specimens with and without inclusion, the proposed model exhibits excellent capability in fatigue life prediction for a wide range of stress ratio. This work draws insights on physics-based life prediction for inclusion induced fatigue failure. Graphical abstract: Unlabelled Image Highlights: A mesoscale stress-life criterion is proposed for bi-phase Ti alloy containing inclusion. Molecular dynamics is employed to determine the dislocation slip properties. Crystal plasticity FEM is used to evaluate the mesoscale stress alteration. Model validation is realized by LCF and HCF test with a wide range of stress ratios.